Losing control: excessive alcohol seeking after selective inactivation of cue-responsive neurons in the infralimbic cortex - Pfarr, Simone; Bartsch, Dusan; Spanagel, Rainer; Sommer, Wolfgang H. (The journal of neuroscience, 2015)
Loss of control over drinking is a key deficit in alcoholism causally associated with malfunction of the medial prefrontal cortex (mPFC), but underlying molecular and cellular mechanisms remain unclear. Cue-induced reinstatement of alcohol seeking activates a subset of mPFC neurons in rats, identified by their common expression of the activity marker cFos and comprised of both principal and interneurons. Here, we used cFos-lacZ and pCAG-lacZ transgenic rats for activity-dependent or nonselective inactivation of neurons, respectively, which by their lacZ encoded β-galactosidase activity convert the inactive prodrug Daun02 into the neurotoxin daunorubicin. We report that activity-dependent ablation of a neuronal ensemble in the infralimbic but not the prelimbic subregion induced excessive alcohol seeking. The targeted neuronal ensemble was specific for the cue-induced response because stress-induced reinstatement was not affected in these animals. Importantly, nonselective inactivation of infralimbic neurons, using pCAG-lacZ rats, was without functional consequence on the cue-induced reinstatement task. Thus, inhibitory control over alcohol seeking is exerted by distinct functional ensembles within the infralimbic cortex rather than by a general inhibitory tone of this region on the behavioral output. This indicates a high level of functional compartmentation within the rat mPFC whereat many functional ensembles could coexist and interact within the same subregion.